Edge states of hydrogen terminated monolayer materials: silicene, germanene and stanene ribbons. (7th February 2017) - Hattori, Ayami; Tanaya, Sho; Yada, Keiji; Araidai, Masaaki; Sato, Masatoshi; Hatsugai, Yasuhiro; Shiraishi, Kenji; Tanaka, Yukio
Abstract: We investigate the energy dispersion of the edge states in zigzag silicene, germanene and stanene nanoribbons with and without hydrogen termination based on a multi-orbital tight-binding model. Since the low buckled structures are crucial for these materials, both the π and σ orbitals have a strong influence on the edge states, different from the case for graphene nanoribbons. The obtained dispersion of helical edge states is nonlinear, similar to that obtained by first-principles calculations. On the other hand, the dispersion derived from the single-orbital tight-binding model is always linear. Therefore, we find that the non-linearity comes from the multi-orbital effects, and accurate results cannot be obtained by the single-orbital model but can be obtained by the multi-orbital tight-binding model. We show that the multi-orbital model is essential for correctly understanding the dispersion of the edge states in tetragen nanoribbons with a low buckled geometry.